2007
DOI: 10.1097/01.sla.0000245833.48399.9a
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Following Breast Cancer Surgery in Women

Abstract: Morbidity and mortality rates following BCS in women are low, limiting their value in assessing quality of care. Mastectomy carries higher complication rate than l-ANP with wound infection being the most common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
137
7
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(165 citation statements)
references
References 16 publications
16
137
7
5
Order By: Relevance
“…[19] The survey found that cardiac and pulmonary complications, while more frequent in patients undergoing mastectomy than lumpectomy, were nevertheless uncommon. In fact, in their report no cardiac or pulmonary complications occurred in 1441 patients undergoing lumpectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[19] The survey found that cardiac and pulmonary complications, while more frequent in patients undergoing mastectomy than lumpectomy, were nevertheless uncommon. In fact, in their report no cardiac or pulmonary complications occurred in 1441 patients undergoing lumpectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients have a greater incidence of co-morbidity and functional dependence [16] and in certain circumstances reduced fitness and/or life expectancy may demand modifications from standard treatment. Surgery for breast cancer has very low mortality [18] and deaths directly due to surgery are rare, therefore it can be argued that life expectancy is more important than fitness for surgery in considering treatment options, whether the patient will survive long enough to benefit from the treatment offered. Thorough assessments and analysis of risks/benefits involved should guide treatment decisions in older patients, to ensure that they receive optimal treatment for their breast cancer.…”
Section: Treatment Of Early Breast Cancer 141 Standard Treatment Anmentioning
confidence: 99%
“…Renal & Gynaecological cancers), breast cancer surgery has a low morbidity and mortality; even in elderly patients mortality ranges from 0-0.3% [18,26,27]. Many older patients, who are unfit for general anaesthesia, can have the surgery under local anaesthetic.…”
Section: Surgery In Older Breast Cancer Patientsmentioning
confidence: 99%
“…Patient satisfaction with the surgical outcome becomes operational, given the agreement between expected and perceived outcomes of surgery [23]. The perceived outcome of surgery, in fact, is what is perceived from the post-surgery result by the person.…”
Section: Introductionmentioning
confidence: 99%
“…The perceived outcome of surgery, in fact, is what is perceived from the post-surgery result by the person. Like the surgery of any other organ of the body, mastectomy is followed by consequences that can manifest themselves in many medical, psychological and social aspects [23].…”
Section: Introductionmentioning
confidence: 99%